2006
DOI: 10.1038/sj.npp.1301066
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Teratogenicity Induced by Nonforced Maternal Nicotine Consumption

Abstract: Prenatal nicotine exposure (PNE) has been associated with increased prevalence of attention deficit hyperactivity disorder (ADHD), major depressive disorder (MDD) and substance abuse in exposed children and adolescents. Whether these syndromes are caused by nicotine exposure, or genetic and psychosocial adversities associated with maternal smoking is not completely clear. Animal models suggest a direct impact of PNE. However, the fact that nicotine is forcefully administrated in these paradigms raises some que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
94
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 38 publications
(41 reference statements)
14
94
0
Order By: Relevance
“…In addition, experiments that have administered nicotine via drinking water at doses comparable to ours have found plasma nicotine levels between 21 and 60 ng/ml (Paz et al, 2007;Schneider et al, 2010). Our mothers consumed an average of 5.93 mg/kg/day of nicotine during pregnancy, which is within the range shown to produce behavioral deficits in offspring without causing physical impairments (Paz et al, 2007;Schneider et al, 2010). Nicotine-exposed mothers in the present experiment consumed significantly less water than controls during pregnancy (98.89 ml/kg/day; 131 ml/kg/day; t-test; Po0.01) and gained weight at a slower rate prior to pregnancy (0.21% gain per day; 0.68% gain per day; t-test; Po0.01), characteristics that have been observed before by Schneider et al (2010).…”
Section: Prenatal Nicotine Exposuresupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, experiments that have administered nicotine via drinking water at doses comparable to ours have found plasma nicotine levels between 21 and 60 ng/ml (Paz et al, 2007;Schneider et al, 2010). Our mothers consumed an average of 5.93 mg/kg/day of nicotine during pregnancy, which is within the range shown to produce behavioral deficits in offspring without causing physical impairments (Paz et al, 2007;Schneider et al, 2010). Nicotine-exposed mothers in the present experiment consumed significantly less water than controls during pregnancy (98.89 ml/kg/day; 131 ml/kg/day; t-test; Po0.01) and gained weight at a slower rate prior to pregnancy (0.21% gain per day; 0.68% gain per day; t-test; Po0.01), characteristics that have been observed before by Schneider et al (2010).…”
Section: Prenatal Nicotine Exposuresupporting
confidence: 74%
“…The range of nicotine between 1 and 6 mg/ kg/day has been shown to produce plasma nicotine levels in the range of 10-50 ng/ml in habitual smokers (Benowitz and Jacob, 1987). In addition, experiments that have administered nicotine via drinking water at doses comparable to ours have found plasma nicotine levels between 21 and 60 ng/ml (Paz et al, 2007;Schneider et al, 2010). Our mothers consumed an average of 5.93 mg/kg/day of nicotine during pregnancy, which is within the range shown to produce behavioral deficits in offspring without causing physical impairments (Paz et al, 2007;Schneider et al, 2010).…”
Section: Prenatal Nicotine Exposuresupporting
confidence: 65%
“…Furthermore, such females exhibit greater locomotor sensitization in response to cocaine challenge after a period of drug withdrawal (Franke et al, 2007). Prenatal nicotine exposure has also been shown to increase cocaine reward in both male and female mice (Paz et al, 2007), and to increase total cocaine intake in self-administration tests in male rats (Franke et al, in press). As well as alterations in response to abused drugs, prenatally exposed animals also show decreased initial drive to obtain a natural food reward, sucrose (Franke et al, in press).…”
Section: Behavioral Disordersmentioning
confidence: 99%
“…Whether these syndromes are caused by nicotine (smoke) exposure itself or by genetic and psychosocial mechanisms is still not completely elucidated. 54 Studies have provided a correlation of teratogenic effects of alcohol and tobacco, and the risk of anorectal atresia. Animal researches have suggested that caffeine may potentiate the teratogenicity of these agents.…”
mentioning
confidence: 99%